"Glocalisation" of the English Language: A Cultural Linguistics Perspective (KEMANUSIAAN The Asian Journal of Humanities, 2016)
In line with other aspects of globalisation, the unprecedented global spread of English has led to an increase in the degree to which the language has become localised, serving to encode the communicate needs of various speech communities. This dual process of globalisation and localisation of English may be referred to as the "glocalisation" of the language. Glocalisation of English involves various processes at the level of "cultural conceptualisations". These include: (1) the use of English to encode cultural conceptualisations that were not originally associated with the language, (2) spread of Anglo-English cultural conceptualisations to non-Anglo speech communities and (3) blending of cultural conceptualisations. This article elaborates on these processes and discusses the implications of the glocalisation of English for the field of Teaching English to Speakers of Other Languages (TESOL).